First Language Acquisition at Your Fingertips: A Digital Flipbook Resource for Pre-Service English Teachers - Rima, Rosmania; Yayat Ruhiat; Lukman Nulhakim (Universitas Hamzanwadi, 2024)
Pre-service English teachers (PSETs) often encounter challenges translating theoretical knowledge of Foreign Language Acquisition (FLA) principles into practical classroom applications, impacting their confidence and readiness for teaching. To address this issue, this study examines creating and assessing a digital flipbook developed as a targeted learning resource to enhance PSETs' ability to connect theoretical knowledge with practical teaching applications. The flipbook was designed to incorporate multimedia features, interactive activities, and learner-centered principles, providing PSETs with an engaging and practical learning resource. The study utilized the 4D model to guide the design and development process, involving 30 third-year PSETs at Sultan Ageng Tirtayasa University. Expert validation of the flipbook's design, content, and language yielded a score of 4.75, categorized as